Age at menarche and performance intelligence quotients of adolescents in Bangkok, Thailand: a cross-sectional study. Issue 1 (December 2016) - Noipayak, Pongsak; Rawdaree, Petch; Supawattanabodee, Busaba; Manusirivitthaya, Sumonmal
Abstract Background The presence of an association between age at the onset of puberty and intelligence quotient (IQ) in young adolescents remains controversial. The aim of this study was to explore the association between age at menarche and performance IQ scores of young female adolescents in Bangkok, Thailand. Methods A cross-sectional study was conducted among 537 students aged 11–15 years attending primary and secondary schools in the Dusit district of Bangkok, Thailand. The participants were selected based on two-step stratified sampling. Age at menarche and health and socioeconomic status were determined using a self-report questionnaire completed by participants. Performance IQ scores were determined using the Standard Progressive Matrices intelligence test (Thai version) administered by registered clinical psychologists. Results Of the 537 participants, 0.4 had reached menarche at 8 years of age, 1.9 at 9 years, 10.1 at 10 years, 36.1 at 11 years, 37.6 at 12 years, 10.4 at 13 years, 3.4 at 14 years, and 0.2 % at 15 years. Age at menarche was inversely correlated with performance IQ (Pearson correlation −0.087, p = 0.047). The regression equation predicting performance IQ by age at menarche was performance IQ = 128.06 − 1.16*age at menarche (R 2 = 0.008). In univariate analysis, performance IQ was inversely correlated with age at menarche, body mass index (BMI), time spent watching television, and time sleeping, but was directly correlated with maternal age at birth (allp < 0.05). In multivariate analysis, age at menarche and BMI remained significantly inversely correlated with performance IQ (p < 0.05), while maternal age at birth was directly correlated with performance IQ. The model consisting of age at menarche, BMI, and maternal age at birth best predicted performance IQ. Conclusion After adjusting for confounders, multiple regression analysis showed that age at menarche and BMI of young female adolescents living in the Dusit district of Bangkok, Thailand, were inversely correlated with performance IQ, whereas maternal age at birth was directly correlated with performance IQ.